Immune dysfunction in the presence of residual splenic tissue. Issue 7 (July 1982) - Cohen, R C; Ferrante, A
Abstract : Immunological function was examined in children who had undergone splenectomy, in 8 for trauma, and in 11 for haematologic/oncologic reasons. Particular emphasis was placed on the effects of residual splenic tissue on immune function. Children in the elective group had no evidence of splenosis but 6 of the 8 trauma patients showed residual splenic activity. A general trend indicated that immunological dysfunction was associated with the presence of residual splenic tissue. Three patients with significant post-traumatic splenosis showed low IgM levels, one also had a low IgG level and another a low IgA and impaired lymphocyte response to mitogens. The trauma patients with little or no splenic tissue had normal immune functions. Immunological abnormalities were found in 8 of the 11 haematologic/oncologic patients with no splenosis suggesting the abnormalities were possibly due to the primary disease. In contrast to the popular belief that splenosis confers protection against overwhelming sepsis, the present findings suggest that patients with residual splenic tissue are at a greater risk of infection because of a lower level of immune response.